Interactive typography module in enhancing visual communication pedagogy in teaching visual art education for secondary school / Hazlin Aisha Zainal Abidin - Zainal Abidin, Hazlin Aisha (2014)
Typography is one of the sub-components in visual communication, where the visualization and function of compositional structure of typography can create an effective impact of visual communication for the viewers and readers. Due to the advancement of technology, typography is seen as the essential component in visual design. The Interactive Typography Module was developed in order to give new alternatives to Visual Art teachers to teach visual communication syllabus in the visual art education for Form 4 Secondary School. Developmental Design Research (DDR) adapted by Richey and Klein (2007) has been used in this research. Phase 1 of need analysis was conducted in the form of in-depth interviews to five Visual Art teachers. Data from the in-depth interview were used for the Surveys that have been conducted in the form of Two Round Delphi Technique distributed to 15 experts from various fields of art and design. The Interactive Typography Module was developed in the form of Typography Module, Interactive Power Point Slide Presentation (PPT), as well as Lesson Plan for teaching Typography. The evaluation phase was conducted by 3 experts from Visual Art Education background in order to look at the levels of usability of the Module. The finding shows that the Interactive Typography Module is undoubtedly suitable to be used as the teaching aids in assisting teachers to teach visual communication syllabus.